A SKYSCRAPER MOSAIC ALGORITHM BASED ON SIFT - Bhagyashri R. Pandurangi; Keshav Y. Patil (International Journal of Innovations in Engineering Research and Technology, 2021)
This project concerns the problem of standing skyscraper image mosaic based on SIFT. In standing skyscraper calculation based on image enhancement or image processing, the first aim is to take picture of the deliberate tall building. Due to some special tall building, or incomplete by geographical conditions, it is impossible to capture complete image of the tall building at one time, and need to shoot sequence tall building images with overlapped areas and stitch them. Here a building picture mosaic method based on SIFT (Scale Invariant Feature Transform) was put ahead. Firstly, the SIFT characteristic vector of every picture was calculated and the feature points are matched using SIFT features. Then the standpoint transform was carried out to the image which was attached by selected four pixels. Finally, the sequence images are stitched based on weighted feature. The experiment of true building image sequence stitching achieves the enhanced flat mosaic effect and show this technique is successful.